Morphology of hair of two-and three-toed sloths (Edentata: Bradypodidae) - Wujek, Daniel E.; Cocuzza, Joan M. (Revista de Biología Tropical, 1986)
Micromorphological differences between hairs of the two-toed sloth (Choloepus hoffmanni) and of the three-toed sloth (Bradypus variegatus) were observed by means of scanning electron microscopy. Hairs of the two-toed sloth had longitudinal grooves which exposed a uniform cortex when viewed in cross section. Hairs of the three-toed sloth have irregular transverse fissures and a cortex that contains scattered fusi. These morphological differences support the placement of the two sloth genera into separate familes. Hairs of four other xenarthran species are al so illustrated.